Bulungan ethnobiology handbook - Puri, R.K. (Center for International Forestry Research, 2001)
This book is intended as a resource for researchers working in the Bulungan area, including the Kayan Mentarang National Park and the Bulungan Research Project (BRF), it serves as both a field guide to common plants and animals, and a dictionary of their vernacular terms from 18 different linguistic/cultural groups. It facilitates communication about familiar flora and fauna among residents of the Bulungan. Finally, this book provides the basis for future analyses of regional patterns of resource use, ethobiological classification, and comparative and historical linguistics. The handbook is divided into several sections containing a variety of formats and types of data. The first two sections present profiles of 164 plants and 111 animal types of data. Each profile page consists of an entry with photograph or illustration and both biological and ethobiological data. The rationale for choosing the survey methods is explained in the section Documenting regional ethnobiology. It is completed with environmental glossary and indexes to scientific names and vernacular names of plants and animals. (YS)